# math

which pair of expressions are equivalent
A 4(6X) and 10X
B 4(6X) and 24X
C 4X + 6X and 10 XX
D 4X + 6X and 24X

1. 👍 0
2. 👎 0
3. 👁 137
1. B

1. 👍 0
2. 👎 0

## Similar Questions

1. ### math

Mr. Howard wrote the following expressions on the board in order to determine which expressions are equivalent and how they are equivalent. 60x+24, 3(20x+8, 4(15x+6) Explain which of these expressions are equivalent using

asked by Jonie on February 18, 2015
2. ### math

Mr. Howard wrote the following expressions on the board in order to determine which expressions are equivalent and how they are equivalent. 60x+24, 3(20x+8, 4(15x+6) Explain which of these expressions are equivalent using

asked by pamela on February 18, 2015
3. ### Algebra

Find a polynomial of degree 4 with i as a zero of multiplicity 1, – i as a zero of multiplicity 1, and 5 as a zero of multiplicity 2. A. x^4 – 10x^3 + 26x^2 – 10x + 25 B. x^4 – 10x^3 + 24x^2 + 10x – 25 C. x^4 – 24x^2 +

asked by Cassie on July 22, 2009
4. ### algebra

Did I do this problem the correct way if so is there a shorter way to explain this? x(x + 6)(x + -4) = 24x x(6 + x)(x + -4) = 24x x(6 + x)(-4 + x) = 24x (6 + x) * (-4 + x x(6(-4 + x) + x(-4 + x)) = 24x x((-4 * 6 + x * 6) + x(-4 +

asked by SO LOST on February 2, 2011

* I don't get this problem at all... 4(x+2) 6x^2 ------ * ---- 5x 2x what are the directions? in the denominator, you have 10x^2 in the numerator, you have 24x^2(x+2) the x^2 divides out, and the numbers can be reduced. that would

asked by Margie on February 21, 2007
6. ### Math

Solve each equation by completing the square. -36x=8x^2+28 -8x^2-3x=-5 5x^2-x-6=0 6x^2-24x-30=0 7x^2+8x-12=0 -10x^2 -9x+1=0 5x^2-x=4 -11x^2-8x=-7x-10 -3 1/3x^2+ 10x -27 1/2= -231/3

asked by Monte' on November 10, 2007
7. ### Math

Solve each equation by completing the square. -36x=8x^2+28 -8x^2-3x=-5 5x^2-x-6=0 6x^2-24x-30=0 7x^2+8x-12=0 -10x^2 -9x+1=0 5x^2-x=4 -11x^2-8x=-7x-10 -3 1/3x^2+ 10x -27 1/2= -231/3

asked by Monte' on November 10, 2007

1.-3f^2+4f-3+8f^2+7f+1 a.5f^2-11f+2 b.11f^2+11f+2*** c.5f^2+11f-2 d.-5f+3f-2 2.3x^2+5X-5X^2-4X-2 a.-8x^2-9x+3 b.2x^2+x+3 c.-2x^2-9x+3 d.-2x^2+x+3*** 3.(8x-2y)+(3x-4y) a.11x+8y*** b.4x-y c.11x-6y d.5x+2y 4.(y+3d)-(-9y+7d) a.-10y+4d

asked by Connexus on May 10, 2016